Routinergency: Domestic securitization in contemporary Israel. (August 2017) - Shapiro, Matan; Bird-David, Nurit
The Israeli law obliges the construction of bomb shelters as integrated rooms within every residential unit throughout the country. Based on 12 months of fieldwork and extensive interviews with both Jewish–Israeli and Arab–Palestinian citizens of Israel, we argue that the mundane presence and use of these everyday-cum-security spaces has produced a new civilian sensibility towards securitization, which we call ' routinergency ': the naturalization of security emergency as intrinsic to the flow of routine life. We demonstrate that while the privatization of domestic securitization affords reliable protection to every citizen, routinergency also excludes Arab–Palestinians from the ethnonational boundaries that still inform the constitution of collective identities in Israel. Yet, as embodied practice, routinergency also enables access to a universal form of citizenship in Israel, which is premised on socioeconomic criticism of Zionist discourse. We use the topological metaphor of a Mobius strip to discuss how mamad rooms accentuate the contemporary tension in Israel between these ethnonational and neoliberal vectors of citizenship.